In absence of money: a field experiment on volunteer work motivation - Vanessa Mertins; Christian Walter (Experimental Economics, 2020)
Although volunteers are a critical resource for non-profit organizations, little is known about how best to motivate them to work. A non-profit organization asked episodic volunteers to produce handmade greeting cards to sell at a fundraising event. By running a natural field experiment, we study the effect of motivating these volunteers through (a) the opportunity to vote on how the money that was raised would be spent and (b) the prospect of individual performance feedback. We find an economically and statistically significant positive effect of both tools on the quantity of work done, while the quality is mostly unaffected. Moreover, we observe significant gender differences in responsiveness to the treatments. While the prospect for feedback is more motivating to men, women respond more strongly to the opportunity to decide how the money would be spent. Empowerment seems to be a simple way to increase engagement for people with low enjoyment.
Keywords: C93; D64; L30; M54; 330; Autonomy; Feedback; Field experiment; Motivation; Volunteering